Regulatory Model and Minimum Safeguards for Conditional Prosecution in Corruption Cases - Angga Rizky Bagaskoro; Prija Djatmika; Faizin Sulistio (Jurnal Wawasan Yuridika, 2025)
The enactment of Law No. 20 of 2025 on the Criminal Procedure Code has provided a legal basis for deferred prosecution agreements. However, their application in corruption cases still raises questions concerning the limits and minimum safeguards required to prevent prosecutorial discretion from developing into selective leniency. This article examines the juridical implications of conditional prosecution in corruption cases and formulates a regulatory model and minimum safeguards compatible with Indonesia’s anti-corruption framework. This study employs normative legal research using statutory, conceptual, and comparative approaches by examining the United States, the United Kingdom, France, and Singapore. The findings show that the recognition of deferred prosecution agreements must be accompanied by rules that limit the cases eligible for this mechanism and ensure accountability in its implementation. The proposed model places the procedural basis within criminal procedure law, while corruption-specific safeguards are regulated through the anti-corruption regime and technical prosecutorial guidelines. The novelty of this study lies in the formulation of operational minimum safeguards, including eligibility criteria and mandatory exclusions, verified obligations for the recovery of state losses and compliance, judicial validation, transparency and monitoring, as well as legal consequences for breach of the agreement.